Investment managers, ESG and the Israeli-Palestinian conflict. Issue 1 (2nd January 2019) - Harris, Daniel A.
Abstract : Discretionary investment managers, in the business of producing financial returns, are increasingly diverting capital for non-financial reasons. In circumstances where it is perfectly legal to invest in the rejected assets, these decisions are therefore made according to subjectively-drawn ethical standards. A sub-set of investment managers steer capital away from securities issued by companies they regard as facilitating the "illegal occupation" of territory controlled by Israel since 1967. In this article, the author examines the legal framework in England and Wales within which this boycott and divestment activity takes place. He argues that this case illustrates the flaws in current "environmental, social and governance criteria" practice, such that the investment managers are at serious risk of personal liability on multiple grounds.